2012
DOI: 10.1667/rr2699.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low and Chronic Radiation Exposure: A Case-Control Study of Mental Retardation and Cleft Lip/Palate in the Monazite-Bearing Coastal Areas of Southern Kerala

Abstract: A population-based 1:3 age-matched case-control study was conducted during 2006-2009 to assess the role of high-level natural radiation (>1 mSv/year) on congenital mental retardation and cleft lip/palate in the southwest coastal area of Kerala. Dosimetry was carried out in the house where parents resided during conception and the subsequent two trimesters of pregnancy of the study subject. Conditional logistic regression did not suggest any statistically significant association of either mental retardation (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Several investigations have been carried out in this area, which includes studies in wild rats[ 5 ], plants [ 6 , 7 ], demographic characterization of human population[ 8 ]. In addition, epidemiological studies are carried out to find out cancer incidence in adults, congenital anomalies in newborns and a case control study of mental retardation and cleft lip/palate in this population [ 9 , 10 , 11 , 12 , 13 ]. So far, no significant changes are observed at phenotype level.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations have been carried out in this area, which includes studies in wild rats[ 5 ], plants [ 6 , 7 ], demographic characterization of human population[ 8 ]. In addition, epidemiological studies are carried out to find out cancer incidence in adults, congenital anomalies in newborns and a case control study of mental retardation and cleft lip/palate in this population [ 9 , 10 , 11 , 12 , 13 ]. So far, no significant changes are observed at phenotype level.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of both cleft lip/palate and hypospadias appeared to be sporadic without association with any of the parameters like maternal age at birth, gravida status, consanguinity, ethnicity, or background radiation dose levels. The population based 1:3 agematched case-control study in the high and normallevel radiation areas of Kerala also did not reveal any association of cleft lip/palate with the prevailing dose levels at parental residences (Koya et al 2012). More than 95 % (145/152) newborns identified with hypospadias were without any other major anomalies.…”
Section: Discussionmentioning
confidence: 82%
“…The present findings, however, are in agreement with the studies elsewhere including those on children born to parents of survivors of atomic bombings (Neel et al 1990), where no statistically significant difference was seen in the frequency of genetic defects between exposed and control groups and at present there is no evidence to suggest any statistically significant association of either stillbirth or MCA with high background radiation. More focused and analytical studies with rigorous dosimetry are being carried out with selected MCAs (Koya et al 2012) and further nested case-control studies with MCA like hypospadias, clubfoot, and other MCA that are very difficult to identify/ diagnose in the field are being planned.…”
Section: Discussionmentioning
confidence: 99%
“…NSCL/P is a complex innate craniofacial abnormality with a multifactorial etiology involving genetic and environmental factors. Several environmental risk factors, such as tobacco, alcohol, and drug use and radiation exposure, have been proven to increase the risk of NSCL/P during the first trimester of pregnancy (Puho et al, ; Leite and Koifman, ; Koya et al, ). On the other hand, other studies have shown that supplementary of folic acid or vitamin in the first trimester of pregnancy can reduce the NSCL/P risk (Goh et al, ; Wehby and Murray, ; Kelly et al, ).…”
Section: Discussionmentioning
confidence: 99%